1975
DOI: 10.5962/bhl.title.3340
|View full text |Cite
|
Sign up to set email alerts
|

Chapters in the prehistory of Eastern Arizona, Paul S. Martin, et al.

Abstract: A tentative alluvial sequence of Hay Hollow Valley 2. Correlation coefficients, r and rho, of the total numbers of plants by species by microhabitats 3. Correlation coefficients, r, of numbers of plants by species by microhabitats using mean data 4. Correlation coefficients, r and rho, of animal densities by microhabitat ... 5. Total plant distribution for all quadrats by microhabitat 6. Total animal transect data 7. Total animal transect data by density per square mile 8. Burial information chart 9. Partial b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
2
1

Year Published

1980
1980
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(79 citation statements)
references
References 21 publications
5
71
2
1
Order By: Relevance
“…The main drawback of our model is that it predicts a low HCN ν 2 = 1 f J = 4 − 3 to J = 3 − 2 flux ratio of 1.7 owing to the extreme column densities, while the observed value is 2.0 ± 0.16 (Martín et al 2016). Arp 220E: the eastern nucleus of Arp 220 has been also imaged with high angular resolution in the (sub)millimeter.…”
Section: Comparison With Datamentioning
confidence: 89%
See 3 more Smart Citations
“…The main drawback of our model is that it predicts a low HCN ν 2 = 1 f J = 4 − 3 to J = 3 − 2 flux ratio of 1.7 owing to the extreme column densities, while the observed value is 2.0 ± 0.16 (Martín et al 2016). Arp 220E: the eastern nucleus of Arp 220 has been also imaged with high angular resolution in the (sub)millimeter.…”
Section: Comparison With Datamentioning
confidence: 89%
“…Absorption of thermal dust continuum by molecular lines at (sub)millimeter wavelengths has been inferred in several galactic nuclei (e.g. Sakamoto et al 2009;Martín et al 2016;Aladro et al 2018).…”
Section: Spatial Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…East-Central Arizona (see Longacre 1970b;Hill 1970;Schoenweller 1962;Martin 1962). These studies indicated that major settlement.…”
Section: The Environmental Modelmentioning
confidence: 83%